Meeting Funder Compliance - Lara-Cinisomo, Sandraluz; Steinberg, Paul (RAND Corporation, 2023)
Funders financially support nonprofit organizations to further mutual goals of implementing programs and providing services; as such, nonprofits must meet certain compliance requirements. This case study, the first of its kind, examines the management processes of one nonprofit as it strives to meet funder compliance requirements, and presents recommendations and survey instruments to assess and improve the quality and efficiency of these processes.